Inflectional variation in Gothic neuter adjectives - Ratkus, Artūras (Kalbotyra, 2015)
This article examines the evidence of morphological variation in the inflection of neuter nominative and accusative singular adjectives as well as other modifiers in Gothic (shorter nominal vs. longer pronominal forms in -ata) in an effort to test the traditional hypothesis on the principles that underlie the variation and examine the diachronic implications of the use of -ata forms. The discussion is based on a total of 76 examples of -ata. It is shown that -ata forms are found in attributive, substantivised and predicative contexts across the modifier lexicon (including adjectives, the quantifier alls, possessive and demonstrative pronouns, participles, etc.) and prevail in attributive as well as substantivised use. From a diachronic point view, the fact that the bulk of -ata forms are more systematically attested in the quantifier alls ‘all’ (a word that has strong pronominal properties) and possessive pronouns is indicative of the strong inflection being more primary to pronouns. It is then possible to propose a scenario of reconstruction where the strong inflection has been passed on from demonstrative pronouns to prototypical adjectives through pronominal adjectives (such as possessive pronouns and the like). It is suggested that the use of -ata forms is difficult to explain semantically. Instead, the evidence of inflectional variation in identical contexts and the sporadic attestation of -ata across the modifier lexicon suggests that the pronominal form is a marked relic of older usage. The scarcity of predicative -ata forms is argued to be unexceptional; it is shown that it can be explained in terms of the statistics of case usage. This eliminates the need to explain predicative -ata forms away, and the recognition of the fact that their use in Gothic extended to all syntactic contexts typical of adjectives (and other relevant modifiers) indicates that there is no syntactically-conditioned allomorphy in the neuter nominative and accusative singular. Finally, it is suggested that the patterning of -ata forms in relation to the noun, and, in particular, the tendency for these forms to be used in post-position to the head, is indicative of the adjective inflection having been pronominalised in the Germanic proto-language, when the typical pattern of word order in the noun phrase was with modifiers being used in post-position to nouns.
Keywords: Gothic; adjectives; pronominal; morphology; reconstruction